The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s1516-18462010005000028
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação audiológica pré-cirurgia otológica de indivíduos com fissura labiopalatina operada

Abstract: RESUMOObjetivo: descrever as características audiológicas de indivíduos com fissura labiopalatina operada (FLP) e indicação de cirurgia otológica, comparando os grupos quanto ao tipo e grau da perda auditiva, bem como a curva timpanométrica. Método: análise de 150 prontuários, ambos os gêneros, idade igual ou superior a 4 anos, FLP e indicação de cirurgia otológica, divididos em 3 grupos: I -Tubo de ventilação (TV), II -Timpanoplastia e III -Timpanomastoidectomia, analisando aspectos quanto a entrevista audiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Um grande número de indivíduos com FLP apresentam perda auditiva do tipo condutiva de grau leve e bilateral, como sequelas decorrentes das otites médias, muito comum nessa população (Santos, et al, 2011).…”
Section: Resultsunclassified
“…Um grande número de indivíduos com FLP apresentam perda auditiva do tipo condutiva de grau leve e bilateral, como sequelas decorrentes das otites médias, muito comum nessa população (Santos, et al, 2011).…”
Section: Resultsunclassified
“…The relationship between CAP disorders in children with CLP is widely discussed in the literature and has as a causal factor the constant alteration of ME found in these patients. This chronic alteration of ME occurs due to malformation of the eustachian tube, caused by an alteration in the trajectory and insertion of the muscles: tensor and levatorvelipalatini on the ipsilateral hard palate, being that the normality is their insertion bilaterally 7,10 . This alteration brings as consequence the malfunctioning of the eustachian tube that remaining closed most of the time, without ventilation, produces a fluid in the ME and recurrent episodes of otitis media.…”
Section: Discussionmentioning
confidence: 99%
“…The eustachian tubehas communication with the tympanic cavity and the nasopharynx, remaining closed for most of the time, having the functions of balancing the air pressure in the middle ear with atmospheric pressure, protecting against the pressure and secretions coming from the nasopharynx to make the drainage of these secretions, through Tensor VeliPalatini muscle, responsible for opening and closing the eustachian tubeduring swallowing. However, for this function to occur, or this process adequately it is essencialthe integrity of the palate and its structures 7,10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the types of auditory complaint, a study 11 conducted with 150 medical records showed that 83% of the sample had some type of hearing complaint, the most frequent being unilateral or bilateral hearing loss (64%). Otitis and otorrhea (current or previous) were more prevalent in the presurgical groups undergoing tympanoplasty and tympanomastoidectomy.…”
Section: Discussionmentioning
confidence: 99%